Increasing the Potential of MSMEs through Increasing Capabilities in Building Business Identity - Roodhi, Mohammad Najib; Hammad, Rifqi; Abdurrahman, Abdurrahman; Dakwah, Muhammad Mujahid; Muhtarom, Zamroni Alpian (Institut Teknologi Nasional, Bandung, 2024)
The aim of this service activity is to help MSMEs in preparing a good and professional company profile so that MSMEs can increase their competitiveness in the current era of globalization. The problem faced by partners is a lack of knowledge and skills in creating a good and professional company profile. The method used in this activity is in the form of training which is divided into 3 stages, namely preparation, delivery of material and training and discussion. The material presented in this activity is the concept of a company profile, the function of a company profile and how to prepare a company profile. The results of the training activities carried out show that there has been an increase in the knowledge and skills of MSME managers in developing MSMEs.